2013
DOI: 10.1051/meca/2013048
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of a tube based constitutive equation for linear polymer melts with inter-chain tube pressure effect

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…More recently, Jaishankar and McKinley [20] demonstrated that the validity range of the Cox-Merz rule and Gleiisle mirror relations hold in the framework of fractional K-BKZ constitutive equations with a Mittag-Leffler relaxation function. The validity of Cox-Merz rule in the framework of the constitutive equation of Dhole-Leyghe-Bailly-Keunings is also discussed in [21].…”
Section: Rheological Characterizationmentioning
confidence: 99%
“…More recently, Jaishankar and McKinley [20] demonstrated that the validity range of the Cox-Merz rule and Gleiisle mirror relations hold in the framework of fractional K-BKZ constitutive equations with a Mittag-Leffler relaxation function. The validity of Cox-Merz rule in the framework of the constitutive equation of Dhole-Leyghe-Bailly-Keunings is also discussed in [21].…”
Section: Rheological Characterizationmentioning
confidence: 99%